Optimizing Sales Performance of Culinary MSMEs Through Strategic Digital Marketing in the Digital Transformation Era - Fahmia Rahmadilla; Marsofiyati; Eka Dewi Utari (Marketing and Business Strategy, 2025)
This study analyzes the influence of digital marketing strategies on the sales performance of culinary MSMEs in the digital era. The phenomenon shows that digital marketing adoption among culinary MSMEs remains low despite increasing digital market potential. Using a survey of 30 culinary MSME owners, this study examines three strategic components content marketing, social media marketing, and e-commerce marketing and their impact on five sales performance indicators: sales volume, growth, target achievement, new customer acquisition, and customer retention. Regression analysis results indicate that digital marketing strategies significantly affect sales performance, with an R² of 0.322. Social media marketing has the most significant influence, followed by content marketing and e-commerce marketing. These findings contribute to the academic literature by validating the integrated role of digital marketing in enhancing MSME performance. From a managerial perspective, the study implies that culinary MSMEs should prioritize strategic use of social media to enhance brand visibility, develop consistent, engaging content to foster customer trust, and optimize e-commerce platforms to expand market reach. Furthermore, regular analysis of digital metrics and customer engagement data is essential for continuous improvement. Strengthening digital capabilities can enhance competitiveness and accelerate sustainable sales growth in the evolving digital marketplace